2022
DOI: 10.1007/s11661-022-06594-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Characterize and Model Stress-Relaxation Aging Behavior of Aluminum Alloys Under Age Forming Conditions

Abstract: A new method that utilises theories of thermally activated deformation and repeated transient stress-relaxation tests has been proposed and validated in this study for the characterisation and modelling of the stress-relaxation ageing (SRA) behaviour of aluminium alloys and its dependence on stress and temperature. Using the new method, key deformation-related variables, i.e. stress components, activation volume and energy, of the aerospace grade heattreatable aluminium alloy AA7B04 have been obtained as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The apparent activation energy Q a is the important variable required for the creep strain rate modeling as a function of temperature in the SR stage. Li et al [32] have found that the Q a in the elastic region remains almost constant during the RSR experiments of AA7B04 aluminum alloy. The activation energy Q in elastic region is described as follows:…”
Section: Creep Strain Model In Stress Relaxation Stagementioning
confidence: 95%
See 1 more Smart Citation
“…The apparent activation energy Q a is the important variable required for the creep strain rate modeling as a function of temperature in the SR stage. Li et al [32] have found that the Q a in the elastic region remains almost constant during the RSR experiments of AA7B04 aluminum alloy. The activation energy Q in elastic region is described as follows:…”
Section: Creep Strain Model In Stress Relaxation Stagementioning
confidence: 95%
“…These data can be used to characterize and analyze the deformation behavior and mechanism of materials during SR. The creep strain rate .ε c of titanium alloy can be modeled using the following equation[32]:…”
mentioning
confidence: 99%
“…SiCp are evenly distributed in the composites (Figure 6a,b). The shape and size of grains in the composites remain during ageing, as the ageing temperature is not high enough to enable the apparent change of grains [29]. Meanwhile, it can be observed that, after ageing for 20 h, apparent precipitates can be observed in the large scale image of SEM in Figure 6b.…”
Section: Sicp and Microstructural Evolutionmentioning
confidence: 99%
“…Guo [11,12] describes the stress relaxation behavior of copper wires with different diameters by the thermal activation theory, realizes the connection between the physical mechanism and the deformation process in the stress relaxation process, and analyzes and confirms that the interaction between dislocation and grain boundary is the dominant mechanism of stress relaxation. Based on the thermal activation theory and repeated stress relaxation experiments, Li [13] proposed a new constitutive model to predict the stress relaxation behavior of AA7B04 under different temperature and loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure7shows the relationship between strain rate and stress in stress release. According to equation(13), linear fitting is performed for  e s ln ln , p and the strain rate sensitivity coefficient m is the slope of the equation. As shown in the figure, the value range of strain rate sensitivity coefficient is: 0.04845 ∼ 0.3063.…”
mentioning
confidence: 99%